2022
DOI: 10.3390/foods11193128
|View full text |Cite
|
Sign up to set email alerts
|

Will It Cricket? Product Development and Evaluation of Cricket (Acheta domesticus) Powder Replacement in Sausage, Pasta, and Brownies

Abstract: Insect powders used in food products may lower the overall quality when compared to conventional counterparts. This preliminary study was used to develop and evaluate insect-based food products and to utilize them in a future consumer test. Pork sausage, dried pasta, and chocolate brownie formulations were developed to either contain NO cricket powder (Control) or have cricket powder (CP). The products were evaluated for proximate composition and product-dependent parameters. The protein content increased in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 90 publications
1
16
2
Order By: Relevance
“…The decrease in attribute liking of the CP sausage may be attributed to the changes in the quality of the sausage product. Ho et al [ 63 ] found that the CP sausage became darker than the Control and textural changes were found for firmness and springiness. When using cricket powder, Smarzyński et al [ 97 ] found that the addition of cricket powder decreased the lightness of pork pâtés, and shifted the color more towards blue.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The decrease in attribute liking of the CP sausage may be attributed to the changes in the quality of the sausage product. Ho et al [ 63 ] found that the CP sausage became darker than the Control and textural changes were found for firmness and springiness. When using cricket powder, Smarzyński et al [ 97 ] found that the addition of cricket powder decreased the lightness of pork pâtés, and shifted the color more towards blue.…”
Section: Resultsmentioning
confidence: 99%
“…A two-week sensory test was conducted to evaluate the three different products containing cricket ( Acheta domesticus ) powder. A mild Italian-style fresh sausage, dried pasta, and chocolate brownie were developed to either NOT contain cricket powder (Control) or contain cricket powder (CP) by Ho et al [ 63 ]. The three products were evaluated by utilizing them as major components in a three-course meal that included an appetizer (sausage), entrée (pasta), and dessert (brownie).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations